Educating Film Audience Through Social Cognitive Theory Reciprocal Model - Siti Rugayah Tibek; Rosmawati Mohd. Rasit; Salasiah Hanin Hamjah; Fariza Md. Sham; Muhamad Faisal Ashaari; Muhammad Adib Samsudin; ‘Adawiyah Ismail (Elsevier Ltd, 2024)
Procedia - Social and Behavioral Sciences 174 ( 2015 ) 1234 – 1241